2009
DOI: 10.1107/s1600536809014974
|View full text |Cite
|
Sign up to set email alerts
|

(E)-1-Methyl-4-[2-(1-naphthyl)vinyl]pyridinium 4-bromobenzenesulfonate

Abstract: In the title compound, C18H16N+·C6H4BrO3S−, the cation exists in the E configuration and the whole mol­ecule of the cation is disordered with a refined site-occupancy ratio of 0.733 (1):0.267 (1). The naphthalene system is not planar, the inter­planar angle between the two aromatic rings being 5.0 (5)° for the major component and 5.7 (10)° for the minor component. The cation is twisted with dihedral angles between the pyridinium ring and the two aromatic rings of the naphthalene system of 56.3 (5) and 51.4 (5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…The bond lengths are in normal ranges (Allen et al, 1987) and are comparable to those observed in related structures (Chanawanno et al, 2008;Chantrapromma et al, 2006Chantrapromma et al, , 2007Chantrapromma et al, , 2008Chantrapromma et al, , 2009a).…”
Section: S1 Commentsupporting
confidence: 83%
See 1 more Smart Citation
“…The bond lengths are in normal ranges (Allen et al, 1987) and are comparable to those observed in related structures (Chanawanno et al, 2008;Chantrapromma et al, 2006Chantrapromma et al, , 2007Chantrapromma et al, , 2008Chantrapromma et al, , 2009a).…”
Section: S1 Commentsupporting
confidence: 83%
“…Styryl pyridinium derivatives are considered to be good conjugated π-systems (Cheng et al, 1991a(Cheng et al, , 1991b. In our on-going research in searching for NLO materials (Chanawanno et al, 2008;Chantrapromma et al, 2006Chantrapromma et al, , 2007Chantrapromma et al, , 2008Chantrapromma et al, , 2009a, we have previously reported the crystal structure of (E)-1-methyl-4-[2-(1-naphthyl)vinyl]pyridinium 4-bromobenzenesulfonate (Chantrapromma et al, 2009a). In order to study the effect of different positions of the subsituent group and anions, the title compound was synthesized by replacing the 1-naphthyl and 4-bromobenzenesulfonate in the (E)-1-methyl-4-[2-(1-naphthyl)vinyl]pyridinium 4-bromobenzenesulfonate with 2-naphthyl and iodide in the title compound.…”
Section: S1 Commentmentioning
confidence: 99%
“…For background on non-linear optical materials research, see: ; Cheng, Tam, Stevenson et al (1991). For related structures, see: Chanawanno et al (2008); Chantrapromma et al (2009); Chantrapromma, Rodwatcharapiban & Fun (2006) ;Chantrapromma, Ruanwas et al (2006). For the stability of the temperature controller used in the data collection, see: Cosier & Glazer (1986).…”
Section: Related Literaturementioning
confidence: 99%
“…Styryl pyridinium derivatives are considered to be promising NLO materials Cheng, Tam, Stevenson et al, 1991). During the course of our exploring for new organic NLO materials, we have previously synthesized and reported a number of the crystal structures of pyridinium derivatives (Chanawanno et al, 2008;Chantrapromma, Rodwatcharapiban & Fun, 2006;Chantrapromma, Ruanwas et al, 2006;Chantrapromma et al, 2009). The title compound (I) has been synthesized and its crystal structure is reported here as part of our ongoing research on NLO materials.…”
Section: Related Literaturementioning
confidence: 99%
“…For background to non-linear optical materials research, see: Koshima & Matsuura (1998); Prasad & Williams (1991); Wenseleers et al (1998). For related structures, see: Chanawanno et al (2008); Chantrapromma et al (2007Chantrapromma et al ( , 2008; Chantrapromma, Chanawanno & Fun (2009) ;Chantrapromma, Jansrisewangwong et al (2009). For the stability of the temperature controller used in the data collection, see: Cosier & Glazer (1986).…”
mentioning
confidence: 99%